THE IMMEDIATE IMPACT OF AN INTERACTIVE PASSIVE-VOICE PRACTICE TOOL ON UNIVERSITY EFL LEARNERS: A PILOT PRETEST–POSTTEST STUDY (Eureka Journal of Education & Learning Technologies, 2026)
The passive voice continues to pose significant grammatical challenges for university-level learners of English as a Foreign Language (EFL). Even though students usually know the rules for passive voice at a declarative level, they often have trouble using them correctly and consistently when they are writing. This difficulty is due in part to the fact that passive constructions are morphosyntactically complex and that there aren't enough chances to practice dense, structured production in class.
Keywords: EFL grammar instruction; passive voice; technology-enhanced learning.